PEMIKIRAN KEAGAMAAN DI INDONESIA (ANALISIS TERHADAP KONTESTASI IDEOLOGI KEAGAMAAN) - Nurul Aqidatul Izzah; Poppy Hippy; Barsih Annor; Mahmuddin Mahmuddin (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
The royalty of religious followers toward their religion in negative ways tend to bear such exclusive ideology which produces internal conflict among interreligious people. As Indonesia today’s condition, different understanding and religious practice become a big trouble which is hard to unite so that it causes unforthcoming political flames. Fundamental problem about that is a problem related to different understandings toward state and religion relationship. In one hand, it said that religion constitutes part of state but in other hand, both religion and state are different instead of undivided things. Looking at such phenomenon.